The Human Wallace Line: Racial Science and Political Afterlife. Issue 3 (July 2019) - Sysling, Fenneke
Abstract : This paper examines racial science and its political uses in Southeast Asia. It follows several anthropologists who travelled to east Nusa Tenggara (the Timor Archipelago, including the islands of Timor, Flores and Sumba), where Alfred Russel Wallace had drawn a dividing line between the races of the east and the west of the archipelago. These medically trained anthropologists aimed to find out if the Wallace Line could be more precisely defined with measurements of the human body. The paper shows how anthropologists failed to find definite markers to quantify the difference between Malay and Papuan/Melanesian. This, however, did not diminish the conceptual power of the Wallace Line, as the idea of a boundary between Malays and Papuans was taken up in the political arena during the West New Guinea dispute and was employed as a political tool by all parties involved. It shows how colonial and racial concepts can be appropriated by local actors and dismissed or emphasised depending on political perspectives.